Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.

Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis